Design of a Web-Based Point of Sale (POS) System with Stock Management and Sales Reports at Zeals Sport Store - Muhammad Andre Wahyudi; Ruly Dwi Arista; Juliandri (Cattleya Darmaya Fortuna, 2026)
The rapid development of information technology has transformed the way retail businesses manage sales transactions and inventory. However, many retail stores still rely on manual methods, such as notebooks and spreadsheets, to record sales and stock data. These conventional practices often lead to recording errors, inaccurate inventory information, delayed report generation, and inefficiencies in daily operations. As a result, business owners face difficulties in monitoring stock availability and making informed managerial decisions. Similar issues have been identified in previous studies, which suggest that web-based Point of Sale (POS) systems can improve transaction management by providing automated and integrated data processing. A POS system not only facilitates the sales transaction process but also supports inventory control, reduces human errors, and generates accurate sales reports in a timely manner. Therefore, Zeals Sport requires a web-based POS system equipped with inventory management and sales reporting features. The implementation of this system is expected to enhance operational efficiency, improve data accuracy, accelerate the payment process, and provide reliable information to support business decision-making.